Article Review: Pendekatan Holistik Manajemen Obesitas: Aspek Psikologis dan Kesehatan Mental - Syarel, Radin Ghefira Naura; Berawi, Khairun Nisa; Febriani, Wiwi (CV. Jasa Sukses Abadi, 2024)
Obesity is a complicated and multifaceted medical disorder defined by excess fat buildup, which can have a severe impact on an individual's physical and mental health. In 2022, the World Health Organization (WHO) reported that around 2.5 billion persons globally are overweight, with obesity incidence in Indonesia reaching 23.1%. This number indicates a notable rise and raises major public health concerns. Obesity has a significant effect on a person's mental health, including sadness, anxiety, and low self-esteem, in addition to raising the risk of several chronic diseases like type 2 diabetes, hypertension, and cardiovascular disease. According to recent studies, psychological variables are crucial in the emergence and maintenance of obesity. Unhealthy eating habits, such as consuming foods high in calories and low in nutrients, can be brought on by stress, social stigma, and environmental pressure. As a result, obesity management requires a multidisciplinary strategy that not only focuses on physical therapies such as food and exercise, but also takes into account the psychological factors that influence eating behavior. Acceptance and Commitment Therapy (ACT), which aims to help people manage psychological stress and build mental resilience, is one promising strategy. Accepting challenging emotional situations and resolving to act in line with one's own ideals are the main goals of ACT. It is believed that removing the stigma attached to weight and offering sufficient psychological assistance can enhance the lives of those who suffer from obesity and stop the rise in obesity rates in Indonesia. Better outcomes in controlling this condition can be accomplished by improving our understanding of the link between mental health and obesity and implementing comprehensive intervention techniques. This comprehensive strategy is anticipated to offer a more successful way to deal with the issue of obesity in society by incorporating a number of academic fields, such as psychology, nutrition, and sports.